Nikon creative lighting system digital field guide - Thomas, J. Dennis (Wiley Pub., 2010)
"Nikon's Creative Lighting System is like having a low-cost, wireless, studio lighting system that's portable enough to fit into a camera bag. Although the possibilities are endless and exciting, setting up, synchronizing the equipment, and determining lighting ratios can be a bit overwhelming. Luckily, this Digital Field Guide has been completely updated to shed some light on the situation! Beginning with the basic functions of the Nikon SB-900, the SB-800, and the SB-600, the author then goes on to demystify the complexities of using multiple speedlights, adjusting flash outputs, and setting up a wireless studio"--Resource description page.